2003
DOI: 10.1021/jo034258u
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Lewis Acidity of Metal Ions with Different Ligands and Counterions in Relation to the Promoting Effects of Lewis Acids on Electron Transfer Reduction of Oxygen

Abstract: The g(zz) values of ESR spectra of superoxide (O(2)(.-) complexes of metal ion salts acting as Lewis acids with different ligands and counterions were determined in acetonitrile at 143 K. The binding energies (DeltaE) of (O(2)(.-)/Lewis acid complexes have been evaluated from deviation of the g(zz) values from the free spin value. The DeltaE value is quite sensitive to the difference in the counterions and ligands of metal ion salts acting as Lewis acids. On the other hand, the fluorescence maxima of the singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 51 publications
(54 reference statements)
8
79
0
Order By: Relevance
“…The calculated OO distance decreases in the order of O 2 .− (1.343 Å) >O 2 .− Li + (1.309 Å) > O 2 .− Mg 2+ (1.297 Å) > O 2 .− Sc 3+ (1.211 Å) as the Δ E value increases 50. The Δ E value can be used as a quantitative measure of the Lewis acidity of not only metal cations with different counter anions but also neutral Lewis acids, such as organotin compounds 56. 57 In the case of Sc 3+ , the Lewis acidity decreases in the order of Sc(OTf) 3 >(TTP)ScCl (TPP 2− =dianion of tetraphenylporphyrin)>(HMPA) 3 Sc(OTf) 3 .…”
Section: Binding Of Redox‐inactive Metal Ions To O2−mentioning
confidence: 99%
“…The calculated OO distance decreases in the order of O 2 .− (1.343 Å) >O 2 .− Li + (1.309 Å) > O 2 .− Mg 2+ (1.297 Å) > O 2 .− Sc 3+ (1.211 Å) as the Δ E value increases 50. The Δ E value can be used as a quantitative measure of the Lewis acidity of not only metal cations with different counter anions but also neutral Lewis acids, such as organotin compounds 56. 57 In the case of Sc 3+ , the Lewis acidity decreases in the order of Sc(OTf) 3 >(TTP)ScCl (TPP 2− =dianion of tetraphenylporphyrin)>(HMPA) 3 Sc(OTf) 3 .…”
Section: Binding Of Redox‐inactive Metal Ions To O2−mentioning
confidence: 99%
“…Such strong binding of O 2 •− to a Lewis acidic Cu(II) center lowers the free energy of the entire process, making Cu(II)-superoxide formation possible. MCET from one-electron reductants to oxygen is related to the Lewis acidity of metal ions [45,46]. Charges and ion radii are important factors to determine the Lewis acidity of metal ions.…”
Section: Kinetics and Thermodynamics Of Formation Of Cu-o2 Complexesmentioning
confidence: 99%
“…Scandium ion, which has the smallest ion radius among the trivalent metal cations, gives the largest Δ E value (1.00 eV) [45]. The Δ E values are directly correlated with the promoting effects of metal ions in electron-transfer reactions [45,46]. However, this method can only be applied to diamagnetic metal ions, since paramagnetic metal ion complexes with O 2 •− do not generally give EPR signals because of antiferromagnetic coupling or unfavorable conditions due to the presence of an S = 1 ground state, as in the case of [(TMG) 3 tren]Cu II (O 2 •− )] + ((TMG) 3 tren = tris(2-( N -tetramethylguanidyl)ethyl)-amine [54].…”
Section: Kinetics and Thermodynamics Of Formation Of Cu-o2 Complexesmentioning
confidence: 99%
“…34 34 or falls between those of Sc(OTf) 3 and Y(OTf) 3 (g zz = 2.0349, DE = 0.85 eV), respectively. 8,34,62 The high Lewis acidity of 3a and 3b is enough to trigger synthetically useful reactions, since the Lewis acids with an DE value larger than 0.88 were presumed to be capable of inducing carbon-carbon bondforming reactions. 45 The Hammett indicator method [63][64][65] was also applied to determine the acidity of the complex 2a-2b and 3a-3b, and it was found that both of these Lewis …”
Section: Characterization Of Air-stable Metallocene Lewis Acidsmentioning
confidence: 99%